KINERJA SATPOL PP KOTA PEKANBARU DALAM MENANGGAPI LAPORAN MASYARAKAT YANG MASUK PADA PUSAT PELAYANAN PENGADUAN PELANGGARAN PERDA DAN PERKADA (P6) TAHUN 2022 - Safira, Sonia; ', Ishak (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
In this research, there are several problem phenomena that will be raised in 2022 in the performance of Satuan Polisi Pamong Praja (Satpol PP) Pekanbaru in responding to public reports submitted of pusat pelayanan pengaduan pelanggaran perda and perkada (P6), namely that there are reports that are not resolved so that the public makes complaints on online media, there were 7 reports that took longer to complete beyond the specified time, namely 14 working days, and the assessment of the Community Satisfaction Index (IKM) for the completion time element had the lowest average value (NRR) and decreased from the previous year. From the above phenomenon, the aim of this research is to determine the performance of Satpol PP in Pekanbaru City to responding public reports submitted to the pusat pelayanan pengaduan pelanggaran perda and perkada (P6) in 2022 and what the inhibiting factors are. This research is descriptive research with a qualitative approach. The types of data are primary data and secondary data, primary data is obtained directly from informants. Data collection techniques were carried out by means of interviews and documentation. The results of this research show that the performance of Satpol PP in Pekanbaru is running as it should, but there are deficiencies in each of the theoretical indicators used, starting from deficiencies in the quality of work, speed of work in the follow-up process, there is no transparency in accountability for incoming reports, the ability of service officers cannot be proven. according to qualifications and not provided with technical service training, as well as internal communication which is only carried out through report documents. There are inhibiting factors in the performance of Satpol PP, namely inadequate budgeting, lack of human resources (SDM) for the investigative unit, lack of operational vehicles and the signature process has not yet used digitalization so it still uses manual signatures. Keywords: Performance of Satpol PP, Pusat Pelayanan Pengaduan Pelanggaran Perda and Perkada (P6), Public Report.